PSXII-35 Establishment of a recombinant Escherichia coli-induced piglet diarrhea model. (7th December 2018) - Wu, T; Lv, Y; Li, X; Zhao, D; Yi, D; Wang, L; Ding, B; Chen, H; Hou, Y
Abstract: Enterotoxigenic Escherichia coli secrete two primary toxins: heat-stable(ST) and heat-labile(LT) enterotoxin, and over two thirds of piglets diarrhea caused by STa-producing ETEC strains. In order to study injury and mechanism of single toxin of STa, this experiment constructed a recombinant E.coli expressing STa and its diarrhea model on 7 days old piglets. In vitro experiment: the host strant E.coli LMG194 and the plasmid pBAD202 were utilized to construct a recombinant E.coli strain expressed STa. The recombinant strain LMG194-STa was confirmed and toxicity was evaluated by co-culturing with IPEC-1 cells. The E.coli wide type strain K88 and the host strainLMG194 were used as positive and negative control separately. The results showed that the toxicity of LMG194-STa was similar as E.coli K88, and much higher than that of E.coli LMG194. In vivo experiment: twenty-four 7 days old piglets were allotted to four treatments: control group, STa group (LMG194-STa), LMG194 group (LMG194), and K88 group (K88). Piglets were fed with commercially available milk-substitutes, challenged with 2x10E.coli strain on day 5, and killed and samples were collected on day 7.Compared with control group, the results showed that: E.coli infection significantly increased diarrhea rates; changed hematological indexes including blood cells, plasma biochemical indices, DAO and D-xylose activities; damaged intestinal mucosal morphology including crypt depth, number of globet cells, density of lymphocytes and lamina propria cell density; substantially reduced activities of antioxidant enzymes and increased oxidative production; substantially altered intestinal gene expression levels involved in injury, inflammatory and transportation; obviously altered intestinal protein expression levels associated with immune, barrier and transportation. In conclusion, piglets diarrhea model caused by LMG194-STa was constructed successfully. The effect evaluation and mechanism research revealed that LMG194-STa induced piglets diarrhea, inflammatory, oxidative stress, intestinal structural and functional damage by changing expression levels of relevant genes and proteins.